Optically Active Nanostructured ZnO Films. (22nd October 2015) - Duan, Yingying; Han, Lu; Zhang, Jialiang; Asahina, Shunsuke; Huang, Zhehao; Shi, Lin; Wang, Bo; Cao, Yuanyuan; Yao, Yuan; Ma, Liguo; Wang, Cui; Dukor, Rina K.; et al.
Abstract: Inorganic nanomaterials endowed with hierarchical chirality could open new horizons in physical theory and applications because of their fascinating properties. Here, we report chiral ZnO films coated on quartz substrates with a hierarchical nanostructure ranging from atomic to micrometer scale. Three levels of hierarchical chirality exist in the ZnO films: helical ZnO crystalline structures that form primary helically coiled nanoplates, secondary helical stacking of these nanoplates, and tertiary nanoscale circinate aggregates formed by several stacked nanoplates. These films exhibited optical activity (OA) at 380 nm and in the range of 200–800 nm and created circularly polarized luminescence centered at 510 nm and Raman OA at 50–1400 cm −1, which was attributed to electronic transitions, scattering, photoluminescent emission, and Raman scattering in a dissymmetric electric field. The unprecedented strong OA could be attributed to multiple light scattering and absorption‐enhanced light harvesting in the hierarchical structures.